Neuropilin-1 Mediates Collapsin-1/Semaphorin III Inhibition of Endothelial Cell Motility: Functional Competition of Collapsin-1 and Vascular Endothelial Growth Factor-165 - Miao, Hua-Quan (The Rockefeller University Press, 1999)
Neuropilin-1 (NRP1) is a receptor for two unrelated ligands with disparate activities, vascular endothelial growth factor-165 (VEGF(165)), an angiogenesis factor, and semaphorin/collapsins, mediators of neuronal guidance. To determine whether semaphorin/collapsins could interact with NRP1 in nonneuronal cells, the effects of recombinant collapsin-1 on endothelial cells (EC) were examined. Collapsin-1 inhibited the motility of porcine aortic EC (PAEC) expressing NRP1 alone; coexpressing KDR and NRP1 (PAEC/KDR/NRP1), but not parental PAEC; or PAEC expressing KDR alone. The motility of PAEC expressing NRP1 was inhibited by 65–75% and this inhibition was abrogated by anti-NRP1 antibody. In contrast, VEGF(165) stimulated the motility of PAEC/KDR/NRP1. When VEGF(165) and collapsin-1 were added simultaneously to PAEC/KDR/NRP1, dorsal root ganglia (DRG), and COS-7/NRP1 cells, they competed with each other in EC motility, DRG collapse, and NRP1-binding assays, respectively, suggesting that the two ligands have overlapping NRP1 binding sites. Collapsin-1 rapidly disrupted the formation of lamellipodia and induced depolymerization of F-actin in an NRP1-dependent manner. In an in vitro angiogenesis assay, collapsin-1 inhibited the capillary sprouting of EC from rat aortic ring segments. These results suggest that collapsin-1 can inhibit EC motility as well as axon motility, that these inhibitory effects on motility are mediated by NRP1, and that VEGF(165) and collapsin-1 compete for NRP1-binding sites.